The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/srt.13351
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted blepharoplasty: An innovative safe and effective technique

Abstract: Background: Blepharoplasty is one of the most popular esthetic procedures with an acceptable risk profile and a relatively quick procedure. Methods:The aim was to evaluate the efficacy and safety of a new CO 2 and 1540-nm laser-assisted blepharoplasty technique applied to the upper and lower eyelids. A total of 38 patients were enrolled. Photographs were taken before the treatment and at 6month follow-up. One "blind" observer assessed the performance of this technique by ranking the results in four categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(79 reference statements)
0
3
0
Order By: Relevance
“… 14 Sometimes, non‐ablative lasers for instance, neodymium: YAG (1320 nm) laser and fractional erbium glass (1550 nm) laser, are used together to reduce the ablative lasers side effects however they have less improvement and need more sessions for treatment. 15 , 16 , 17 , 18 Therefore, this study aimed to investigate the effect of Endolift laser therapy as a novel technique on nasolabial fold and marionette lines (one of the facial danger zones).…”
Section: Introductionmentioning
confidence: 99%
“… 14 Sometimes, non‐ablative lasers for instance, neodymium: YAG (1320 nm) laser and fractional erbium glass (1550 nm) laser, are used together to reduce the ablative lasers side effects however they have less improvement and need more sessions for treatment. 15 , 16 , 17 , 18 Therefore, this study aimed to investigate the effect of Endolift laser therapy as a novel technique on nasolabial fold and marionette lines (one of the facial danger zones).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scanning area can be heated homogeneously, continuously, and without coagulation using the second wavelength of 1540 nm. Recently published studies demonstrated the potential application of this dual-wavelength laser technique (10,600 nm/1540 nm) for post-surgical scar management, extensive hypertrophic burn scar management, and as an efficient laser-assisted blepharoplasty technique with good and promising results [20,21]. In addition, other recent studies showed that this dual-wavelength laser approach has demonstrated promise as a new and safe nonsurgical solution for skin laxity and rejuvenation [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Contraction of the 'old' collagen and stimulation of fibroblasts to make new fibres (elasticity) and proteoglycans (viscoelasticity) lead to an improvement in the tension and density of the skin. Moreover, an innovative study by Bonan et al 13 showed that the combination of the abovementioned wavelengths can be used in a surgical procedure like blepharoplasty.…”
mentioning
confidence: 99%
“…Moreover, an innovative study by Bonan et al. 13 showed that the combination of the abovementioned wavelengths can be used in a surgical procedure like blepharoplasty.…”
mentioning
confidence: 99%